Meningkatkan Keterampilan Menulis Puisi Menggunakan Media Visual Gambar Siswa Kelas IV SDIT Hidayatul Jannah - Rambe, Riris Nurkholida; Ramadani, Karfika Suci; Nisa, Khairun; Adella, Sindy (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to improve the ability to write poetry in grade 4 students at SDIT Hidayatul Jannah and to find out students' difficulties in carrying out poetry writing activities. This type of research used a qualitative descriptive research method. Qualitative research method is a method used to examine the condition of natural objects where the researcher is the key instrument. The research subjects were fourth grade students at SDIT Hidayatul Jannah. Data collection techniques used are observation, interviews and literature/documentation studies. The results showed that the ability to write poetry for fourth grade students at SDIT Hidayatul Jannah was still relatively low, because the language used in writing poetry still used everyday language.